2018
DOI: 10.2478/johr-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

The First Report on Alternate Bearing of Barberry (Berberis vulgaris L.): Change in Total Carbohydrate and Phenolic Contents

Abstract: Barberry (Berberis vulgaris L.) fruit is an important source of anthocyanins and is used for consumption and in medicine. However, fruit production of barberry is not regular. Two experiments in four locations were conducted on this plant to explore if it is alternate bearer and also to investigate carbohydrates and phenolics contents in leaves and shoots during growth season. Evaluation of barberry shrubs in three different location showed strong alternate bearing. The value of leaf number to berry number rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…asperma [2,3]. Although barberries were reported to produce a good crop almost annually [4], we showed that barberry plants are strong alternate bearers, as the alternate bearing index (ABI) ranged from 0.63-0.71 depending on orchard location and from 0.42 to 0.69 depending on plant age [5]; the disorder increases with age and becomes more evident after 20 years [6]. Gibberellic acid has been reported to influence morphological traits, flowering, fruiting and various processes in many fruit crops [7][8][9].…”
Section: Introductionmentioning
confidence: 87%
“…asperma [2,3]. Although barberries were reported to produce a good crop almost annually [4], we showed that barberry plants are strong alternate bearers, as the alternate bearing index (ABI) ranged from 0.63-0.71 depending on orchard location and from 0.42 to 0.69 depending on plant age [5]; the disorder increases with age and becomes more evident after 20 years [6]. Gibberellic acid has been reported to influence morphological traits, flowering, fruiting and various processes in many fruit crops [7][8][9].…”
Section: Introductionmentioning
confidence: 87%